Association of guideline-based antimicrobial therapy and outcomes in healthcare-associated pneumonia. (3rd January 2015) - Rothberg, Michael B.; Zilberberg, Marya D.; Pekow, Penelope S.; Priya, Aruna; Haessler, Sarah; Belforti, Raquel; Skiest, Daniel; Lagu, Tara; Higgins, Thomas L.; Lindenauer, Peter K.
Abstract: Objectives: Guidelines for treatment of healthcare-associated pneumonia (HCAP) recommend empirical therapy with broad-spectrum antimicrobials. Our objective was to examine the association between guideline-based therapy (GBT) and outcomes for patients with HCAP. Patients and methods: We conducted a pharmacoepidemiological cohort study at 346 US hospitals. We included adults hospitalized between July 2007 and June 2010 for HCAP, defined as patients admitted from a nursing home, with end-stage renal disease or immunosuppression, or discharged from a hospital in the previous 90 days. Outcome measures included in-hospital mortality, length of stay and costs. Results: Of 85 097 patients at 346 hospitals, 31 949 (37.5%) received GBT (one agent against MRSA and at least one against Pseudomonas ). Compared with patients who received non-GBT, those who received GBT had a heavier burden of chronic disease and more severe pneumonia. GBT was associated with higher mortality (17.1% versus 7.7%, P < 0.001). Adjustment for demographics, comorbidities, propensity for treatment with GBT and initial severity of disease decreased, but did not eliminate, the association (OR 1.39, 95% CI 1.32–1.47). Using an adaptation of an instrumental variable analysis, GBT was not associated with higher mortality (OR 0.93, 95% CI 0.75–1.16). Adjusted length of stay and costs were also higher with GBT. Conclusions: Among patients who met HCAP criteria, GBT was not associated with lower adjusted mortality, length of stay or costs in any analyses. Better criteria are needed to identify patients at risk for MDR infections who might benefit from broad-spectrum antimicrobial coverage.